Microstructure, rheological properties and stability of oleogels derived from palm olein, palm mid fraction and soybean oil blends - Saw, Mei Huey (2020)
Organogelation is an alternative method of structuring edible oils used to produce low saturation solid fat products. Many studies on oleogels involve the use of soft vegetable oils. However, these highly unsaturated oils are mostly thermally unstable and exhibit poor physical properties. Therefore, palm-based liquid oil could be a better choice for the preparation of oleogels due to its balanced fatty acid composition. In oleogel systems, the rheology, stability, physical and microstructural properties of the oleogels are greatly influenced by the preparation temperature and gelator type and dosage, as well as the type of liquid oil used. Therefore, this dissertation focuses on the influence of various factors on the characteristics of palm-based oleogels and the possibility of using palm-based liquid oil in the formation of oleogels. First, gelator screening was conducted through the inverted vial method. Polyglycerol behenice acid ester (PBA), sunflower wax (SFW) and fully hydrogenated palm-based monoacylglycerol with high stearic (MGHO) were selected, whereas fully hydrogenated palm stearin iodine value of 2 (PSIV2), hard palm stearin iodine value of 14 (PSIV14) and fully hydrogenated palm-based monoacylglycerol with high palmitic (MGHP) were removed from further investigation due to their low effectiveness in gelling palm superolein. The results indicated that storage temperature and duration significantly affected the characteristics of the superolein oleogels. Palm superolein tended to crystallize at 5 °C, causing a tremendous increase in the hardness from 1.6 g to 340 g when storage temperature for SFW oleogles was reduced from 25 °C to 5 °C. Similar observation was found for the other oleogels as well due to the crystallization of the superolein at low temperature. At 15 °C, the oleogels derived from SFW and MGHO showed increasing trends in the enthalpy of melting from 4.8 Jg-1 to 7.7 Jg-1 and 9.4 Jg-1 for SFW oleogels and from 7.1 Jg-1 to 12.1 Jg-1 and 14.7 Jg-1 for MGHO oleogels upon storage (from day 1 to day 3) due to the slow crystallization behavior of superolein. PBA oleogels delayed the crystallization of superolein, as no significant changes in properties were observed during the three days of storage. SFW oleogels formed uniform and continuous crystalline structures that efficiently trapped superolein within their structures. Therefore, SFW oleogels were the most stable compared to the other oleogels. In contrast, despite their high hardness (23.1 g) and solid fat content (7.6%), MGHO oleogels were the least stable due to the formation of irregularly sized crystals with loose entanglement. Therefore, MGHO was removed from further investigation due to its poor performance in organogelation. The effects of gelator dosage and liquid oil types on the characteristics of PBA and SFW oleogels were very complicated. The gelator dosage showed positive linear effects on the rheological, thermal and physical properties of PBA and SFW oleogels. However, the gelator dosage effect became less significant when POoIV56 and SBO:PMF (7:3) were used due to their higher saturation content. POP has been identified as a possible key compound in POoIV56 and SBO:PMF (7:3) contributes to differences in the oleogels’ characteristics. The POP in SBO:PMF (7:3) had a higher degree of freedom compared to that in POoIV56 due to its incompatibility with the low-melting TAGs in SBO. Therefore, the POP in the SBO blend had a greater interaction affinity with the PBA and SFW gelators, thus improving the rheological, thermal and physical properties of the oleogels. According to microstructural analysis by XRD, the SFW oleogels derived from SBO and PMF blends exhibited a more complex crystalline system, in which crystals with lamellae sizes of 42.8 Å and 68.9 Å were concurrently present in the oleogel system. This result show that the PMF in the SBO formed cocrystals within the SFW gel structure, and therefore improved the gel strength and stability. The oleogels formed with other liquid oils showed insignificant differences in affecting the oleogels properties. Their GʹLVR, GʺLVR, critical stress, and ΔH values were much lower than those of oleogels formed with POoIV56 and SBO:PMF (7:3). These findings showed that the TAG components in the oils such as POoIV64, POoIV72, SBO, SBO:IV64 (1:1), SBO:PMF (9:1) and SBO:PMF (4:1), did not interfere with the formation of a gel structure; thus, their rheological and thermal profiles were mainly dependent on gelator dosage. In conclusion, the stability of oleogels is attributed to microstructural factors and intermolecular interactions in oleogel formation but is less dependent on the hardness and SFC. This study also showed that PMF could be used to enhance the strength and characteristics of oleogels, especially those of oleogels formed with soft vegetable oils. This study also showed that palm liquid fractions have the potential to be used to form oleogels with satisfactory strength and stability. This new finding could be extended to real food products in the future, whereby palm liquid fractions and blends of PMF with soft vegetable oils could be used as major ingredients in solid fat production to make margarine, shortening replacements and meat products.